Maintaining your belief (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. Today, you'll learn how to maintain belief in yourself, your goals, and your value. We'll look at some aspects of maintaining your belief even during tough times. We'll cover mental strength, resilience, focus, and coaching yourself on your abilities and worth. You'll also learn how to implement key skills, including managing negative thoughts or doubt, dealing with adversity, and staying on course when things are going against you. We'll look at some of the most valuable habits and practices to follow that can maintain your belief and reinforce it over time. Believing in yourself and what you can achieve and building a strong mentality gives you the resilience to withstand negativity and progress towards your long-term career and life goals. Learning Objectives Learn how to maintain belief in yourself, your goals, and your value Learn how to implement key skills, including managing negative thoughts or doubt, dealing with adversity, and staying on course when things are going against you.